Prevalence and clinicopathological characteristics of breast cancer patients with brain metastases in Ghana: A single-center cross-sectional study - Joseph Daniels; Kofi Adesi Kyei; Ronald Walubo; Andrew Yaw Nyantakyi; Edwina Ayaaba Ayabilah; Judith Naa Odey Tackie (PLoS ONE, 2025)
Breast cancer remains a leading cause of cancer-related mortality among women globally. While advances in early diagnosis and systemic therapies have improved survival, they have also increased the likelihood of brain metastases over time, particularly in low-resource settings where limited diagnostic and treatment capacity exacerbates the burden of late-stage disease. The study aimed to determine the prevalence and describe the clinicopathological characteristics of breast cancer patients diagnosed with brain metastasis in a limited-resource healthcare setting. This research was a single-institution-based quantitative cross-sectional study. Socio-demographic, clinical and pathological data were extracted from patients’ medical records as well as the hospital-based cancer registry. Data were analyzed using STATA software (version 16). Descriptive and logistic regression analyses were performed. The study involved 144 adult female metastatic breast cancer patients with a mean age of 48.7 years (SD 11.3). The prevalence of brain metastasis was 17.5%. Only 4.9% presented with de novo brain metastasis, p < 0.001. Bone metastases were present in 31.9% whereas 26.4% and 12.5% had concurrent lung and liver metastasis respectively. In all, 38.9% had grade III tumors. Also, 50.6% were categorized as recursion partition analysis (RPA) class II whereas 49.3% had a performance status of ECOG 2. A considerable majority (86.8%) were treated with palliative intent whereas 13.2% received best supportive care only. In total, 86.8% underwent radiotherapy whereas 81.3% received systemic treatments, with chemotherapy being the most frequently utilized modality (73.5%). Most patients (88%) were treated with 2-dimensional radiotherapy whereas 3.2% received hippocampal-sparing intensity-modulated radiotherapy. The high prevalence of brain metastasis among breast cancer patients with distant metastases reflects the challenges associated with late-stage breast cancer presentation and limited access to advanced diagnostic and therapeutic interventions in limited-resource healthcare settings.